РОЗВИТОК ПІЗНАВАЛЬНОЇ САМОСТІЙНОСТІ УЧНІВ В ІГРОВІЙ ДІЯЛЬНОСТІ (Педагогіка вищої та середньої школи, 2001)
The article deals with the problems of the development of cognitive independence of teenagers in the playing activity the mathematics lessons.